Study on the Influence Factors of Rod Plate Gap Corona Discharge Environment Based on UV Imaging. Issue 1 (3rd December 2020) - Wang, Shenghui; Li, Wei; Jiang, Tingyue; Niu, Leilei; Lv, Fangcheng; Li, Nan
Abstract : To study the influence of environmental factors such as temperature, humidity, wind speed, and air pressure on the detection of corona discharge using ultraviolet imaging, the rod‐plate gap model was used, and the ultraviolet video signals of AC discharge under different environmental conditions were recorded by CoroCAM504 ultraviolet imager, and the environmental factors affecting UV discharge from electrical equipment were analyzed. The experimental results show that the area of the discharge spot increases nonlinearly with temperature. The area of the discharge spot decreases with increasing humidity, and a power‐law relationship governs this behavior. At a humidity of 40 to 90%, the power index varies from 1.6 to 2.6. Wind speed weakens coronal discharge: when the wind speed is 12 m/s and the voltage is 50 kV the discharge spot area is reduced by 76.7% compared with that in still conditions. Air pressure has a significant effect on ultraviolet imaging, and field tests also show that discharge at high altitudes is stronger than that at lower altitude. Based on the above experimental research, normalization of spot area by correction coefficient method is proposed. The correction error is less than 20%, which offers guidance to engineering practice. © 2020 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.